Monarchia teokratyczna Stanisława Orzechowskiego - Gierszewski, Mateusz (Dialogi Polityczne, 2021)
The text contains a presentation and discussion of the views of Stanisław Orzechowski, a Russian priest of the Roman rite, educated at Western universities and involved in political disputes of the nobility under the rule of Sigismund Augustus. He was a writer who stood out from the humanists of the age by his attachment to the Church. He became known as a radical opponent of the Reformation, which he constantly fought against, but at the same time defended the Eastern Churches against unification with Rome. His views led him to formulate a theocratic doctrine of the state, in which the king bound by the coronation oath became subordinate to the archbishop of Gniezno – the primate Polish. He was also a singer of the freedom of the Kingdom of Poland, thanks to which it is the best earthly state. According to him, this happened by combining the classical (pagan) theory of a mixed system with Christian values.